Takeoff: Analysing Pathways for Electric Innovation Facilitation and Regime Destabilisation in the Swedish Aviation Industry - Wimmerström,Kajsa (2021)
Climate change is the greatest challenge of our time. Despite efforts to reduce greenhouse gas (GHG), the emissions contribution from global aviation is set to increase. Electric aviation has emerged as an alternative which could form part of the solution. Sweden, which is on the path to carbon neutrality and has a long history in aviation, could contribute to the global efforts in mitigating climate change through proliferating the electric aircraft. This thesis thus aims to inform the Swedish government on how it can contribute to the development and diffusion of electric aviation. Utilising the technological innovation systems (TIS) framework and lending concepts from the multi-level perspective (MLP), this thesis analyses electric aviation from a wider systems perspective to identify barriers to the development and diffusion of the electric aircraft as well as propose policy instruments to rectify them. Informed through a range of secondary data sources, 14 expert interviews and two observations, this thesis found several problems and underlying structural causes which hinder electric aviation. To spur electric aviation the government could implement a range of policy instruments as well as adjust framework conditions. Creating market incentives, providing infrastructure, and increasing the capacity of government agencies to leverage innovations, as well as creating new networks or balancing the actor-constellation in current networks and facilitating dialogue in them, may be important. Setting a clear agenda and goal is however key. In designing policy instruments and instrument mixes, several design criteria need to be considered as to effectively achieve policy goals. To transition to a new aviation paradigm, there needs to be a simultaneous focus on creation of the new and destruction of the old, and the current landscape changes resulting from the Covid-19 pandemic and increasing awareness of rapid climate change may constitute a window of opportunity to do so.
Keywords: electric aviation; battery-electric aircraft; technological innovation systems (TIS); multi-level perspective (MLP); innovation policy